2022
DOI: 10.1002/ajoc.202100760
|View full text |Cite
|
Sign up to set email alerts
|

One‐pot Synthesis of 3‐Aryliden‐2,3‐dihydro‐4‐quinolones from o‐Anilinopropargyl Alcohols via Aldol Condensation of In Situ Generated 2,3‐Dihydroquinolin‐4‐ones and Aryl Aldehydes

Abstract: A one-pot conversion of o-anilinopropargyl alcohols to 3-aryliden-2,3-dihydro-4-quinolone derivatives with 20 mol% TfOH as the catalyst has been devised. The method may proceed through a sequential Meyer-Schuster rearrangement of o-anilinopropargyls/intramolecular conjugated addition/aldol condensation of in situ generated 2,3-dihydroquinolin-4-ones and aldehydes. Finally, the subsequent additions succeeded between 3-benzyliden-2,3-dihydro-4-quinolones and hydrazines to give fused multicycles. The reaction is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Our previous studies indicated that only primary 3-aryl propargyl alcohols underwent one-pot multi-step transformations smoothly, beginning with the Meyer-Schuster rearrangement. [10,12,13] Very recently, the intramolecular electrophile intercepted Meyer-Schuster rearrangements of secondary and tertiary o-propargyl alcohol benzaldehydes have been reported. [2l,14] On this basis, the present work examined the reactions of sterically-hindered 3-phenyl propargyl alcohols with either one or two À CH 3 groups or one or two Ph groups α to the À OH (Table 4).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous studies indicated that only primary 3-aryl propargyl alcohols underwent one-pot multi-step transformations smoothly, beginning with the Meyer-Schuster rearrangement. [10,12,13] Very recently, the intramolecular electrophile intercepted Meyer-Schuster rearrangements of secondary and tertiary o-propargyl alcohol benzaldehydes have been reported. [2l,14] On this basis, the present work examined the reactions of sterically-hindered 3-phenyl propargyl alcohols with either one or two À CH 3 groups or one or two Ph groups α to the À OH (Table 4).…”
Section: Resultsmentioning
confidence: 99%
“…[9] Recently, our group demonstrated the one-pot synthesis of 3-aryliden-2,3-dihydro-4-quinolones from o-anilinopropargyl alcohols (Scheme 1a). [10] Unfortunately, a condensation reaction between PhCHO and the βaminoketone generated in situ from 1 a and TsNH 2 (Scheme 1b) was not observed. Even so, heating a mixture of 1 a, TsNH 2 and PhCHO readily afforded the aldol-type product 2 a. Multicomponent reactions such as this, in which various reagents are combined in a one pot process to provide high selectivity, efficiency and atom economy, have become increasingly of interest.…”
Section: Introductionmentioning
confidence: 99%
“…A series of 3-aryl substituted propargyl alcohols 1 were synthesized through Pd 2+ -catalyzed Sonogashira coupling reaction of Ar–X and commercially available prop-2-yn-1-ols ( 1a – 1l ), , and aldol condensation and Horner–Wadsworth–Emmons reaction led to trans α,β-unsaturated ketones ( 2a – 2m , 2o – 2q , and 2s ) …”
Section: Resultsmentioning
confidence: 99%
“…The electrophile intercepted Meyer–Schuster rearrangement is associated with the reaction between the nucleophilic allenol and a nonprotic electrophile, which has been described to synthesize various α-functionalized α,β-enones . In the investigation of acid-catalyzed synthesis of carbonyl compounds from propargyl alcohols, a trace amount of dimerization product (2-methylene-1,5-diphenylpentane-1,5-dione) was unexpectedly separated as the byproduct, which may be formed through Meyer–Schuster rearrangement followed by intermolecular Rauhut–Currier reaction (also named intercepted Meyer–Schuster rearrangement, Figure a). To our excitement, addition of chalcone as the electrophilic partner to the reaction of 1a led to a cross-Rauhut–Currier reaction, and 2-methylene-1,3,5-triphenylpentane-1,5-dione 3aa was obtained, and no dimer product was detected.…”
Section: Introductionmentioning
confidence: 99%